## Use the substitution method to solve the following system of equations: 3x + 5y = 3 x + 2y = 0 (1,1) (6,-3) (1

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

## Answers ( )

Answer:(6, – 3 )

Step-by-step explanation:Given the 2 equations

3x + 5y = 3 → (1)

x + 2y = 0 → (2)

Rearrange (2) expressing x in terms of y by subtracting 2y from both sides

x = – 2y → (3)

Substitute x = – 2y into (1)

3(- 2y) + 5y = 3

– 6y + 5y = 3

– y = 3 ( multiply both sides by – 1 )

y = – 3

Substitute y = – 3 into (3) for corresponding value of x

x = – 2(- 3) = 6

Solution is (6, – 3 )